Application of the C5.0 Algorithm to Determine the Level of Public Satisfaction with the E-KTP Recording Service at the Bandar Sub-District Office - Hardani, Dini Fadila; Poningsih; Purba, Yuegilion Pranayama (Journal of Artificial Intelligence and Engineering Applications (JAIEA), 2021)
Community satisfaction at the Bandar Sub-district Office is one of the most important things in assessing the level of e-KTP recording services provided by the agency to the community. The purpose of this study was to determine the quality of the e-KTP recording service at the Bandar Sub-district Office in terms of the Service Procedure, Time, Behavior and Facilities aspects of the Bandar sub-district community. At the Bandar Camat Office these four aspects have not been measured with certainty, so the agency finds it difficult to determine which aspects must be improved. The method used in this study is the C5.0 Algorithm, where the data source used is a questionnaire/questionnaire technique given to the people of Bandar sub-district. The research test process uses Rapid Miner software to create a decision tree. The results of the study obtained 12 rules for classifying the level of community satisfaction with e-KTP recording services. The C5.0 algorithm can be used in cases of community satisfaction with an accuracy rate of 100%. From these results, it is expected to improve the quality of service for the e-KTP recording of the Bandar Sub-District Office to be even better.